Cage‐Like Porous Materials with Simultaneous High C2H2 Storage and Excellent C2H2/CO2 Separation Performance. (30th March 2021) - Di, Zhengyi; Liu, Caiping; Pang, Jiandong; Chen, Cheng; Hu, Falu; Yuan, Daqiang; Wu, Mingyan; Hong, Maochun
Abstract: Adsorption‐based separation is an important technology for C2 H2 purification due to the environmentally friendly and energy‐efficient advantage. In addition to the high selectivity of C2 H2 /CO2, the high uptake of C2 H2 also plays an important role in the separation progress. However, the trade‐off between adsorption capacity and separation performance is still in a dilemma. Herein, we report a series of cage‐like porous materials named FJI‐H8‐R (R=Me, Et, n Pr and i Pr) which all have high C2 H2 uptakes at 1 bar and 298 K. Dynamic breakthrough studies show that they all exhibit excellent C2 H2 /CO2 separation performance. Particularly, FJI‐H8‐Me possesses a long breakthrough time up to 90 min g −1 . Additionally, Grand Canonical Monte Carlo (GCMC) simulation reveals that the suitable pore space and geometry contribute much to the excellent separation performance. Abstract : Cage‐like FJI‐H8‐R (R=Me, Et, n Pr and i Pr) series all exhibit excellent C2 H2 /CO2 separation performance, which may overcome the trade‐off between adsorption capacity and separation performance.